LITERASI PERENCANAAN KEUANGAN SYARIAH PADA ANAK-ANAK PEKERJA MIGRAN INDONESIA DI MALAYSIA - Elis Mediawati; Mimin Widaningsih; Bambang Triyono; Kholis Frendika (Jurnal Abdi Insani, 2025)
Children of Indonesian migrant workers (PMI) in Malaysia face limited access to education due to restrictive policies towards non-citizen children. This community service aims to provide sharia financial planning assistance to PMI children, it is hoped that through this activity children will become more financially literate in sharia. The method used is training on sharia financial planning using workshop, simulation and storytelling methods. The material presented includes the importance of managing school pocket money for needs, saving, giving alms and sharing. The training was conducted offline to PMI children who are members of the At Tanzil Malaysia Learning Studio. The result of this activity is the increased understanding of PMI children about Islamic financial planning. They are expected to apply Islamic financial management principles from an early age, such as managing pocket money, giving zakat, saving, avoiding usury, and planning for the future. With the provision of Islamic financial literacy, PMI children can be better prepared for the future.